A frequency offset compensation method based on all phase FFT amplitude - Yingjie ZHU; Wuxiong ZHANG; Huiyue YI; Hui XU (物联网学报)
Distance measurement is an important part of the wireless location technology.The ranging accuracy of millimeter wave based distance measurement depends on the frequency estimation accuracy of beat signals from the targets, but the existing frequency estimation algorithms have the shortcomings of either high complexity or low accuracy.In order to improve the ranging accuracy, the frequency compensation value and frequency estimation method based on all phase FFT amplitude was proposed to improve the performance of frequency estimation.Firstly, the signal amplitude was estimated based on the relationship between its all phase FFT and its conventional FFT spectrum.Moreover, using the relationship between the estimated signal amplitude, the signal spectrum amplitude and frequency compensation value, the frequency compensation value was solved by Newton iterative algorithm.Then, the frequency compensation value was used to shift the frequency of the signal, and the frequency compensation value was estimated again to obtain the final estimation value of the signal frequency, from which the distance of the target was calculated.Finally, simulation results were presented to show that the proposed method has higher distance measurement accuracy than the existing methods.